Fatimah Az-Zahra: The Ideal Female Figure in the Social Construction of Islam - Opy Putri Melani; Nayla Ramadhani; Indriani; Rusda Karmila; Mustika Sari’ah Siagian (Universitas Insan Budi Utomo, 2026)
Fatimah az-Zahra is recognized as one of the most influential female figures in Islamic civilization. This study discusses Fatimah az-Zahra as an ideal woman in the social construction of Islam by examining her character, moral values, and contributions to family and social life. The purpose of this study is to analyze how Islamic society constructs the image of the ideal woman through the figure of Fatimah az-Zahra and how her example remains relevant in contemporary Muslim life. This research uses a qualitative descriptive method through literature review by examining Islamic books, journals, and historical sources related to Fatimah az-Zahra. The results show that Fatimah az-Zahra represents values of piety, patience, intelligence, modesty, responsibility, and devotion to family and society. In Islamic social construction, she is portrayed not only as a daughter of the Prophet Muhammad, but also as a symbol of women’s dignity, leadership, and moral strength. Her life provides guidance for Muslim women in balancing religious commitment, family responsibilities, and social participation. Therefore, Fatimah az-Zahra continues to serve as an inspirational model for building ethical and harmonious social values in modern Islamic society.